Study of Fuel Inlet Temperature Variations on Palm Biodiesel Operating with a Diesel Engine - M. H. M., Yasin; R., Mamat; Ahmad Fitri, Yusop; M. H., Ali; I., Izzudin (EDP Sciences, 2017)
Biofuel include biodiesel is introduced to overcome the air pollution problems. Biodiesel is the sustainable and alternative fuel that derived from edible and non-edible oil produced from bio-originated species, plants and animals. This paper presents the simulation analysis on the effect of fuel temperature variations on diesel engine performance and emission using palm-biodiesel. A one-dimensional numerical analysis, Diesel RK software is used to simulate a single cylinder, four-stroke diesel engine on the performance and emission when operated at a full load condition using fuel temperature variations ranging 300 K to 333 K. It is found that simulated results for brake power and brake torque were 0.7% each when compared to the highest and lowest fuel temperature ranging from 333 K to 300 K. Moreover, higher fuel temperature for palm biodiesel tend to produce lower exhaust gas temperature and brake specific fuel consumption at a constant engine speed of 2400 rpm. It can be concluded that from the study, fuel temperature variations of biodiesel could produce a significant effect in terms of engine performance and emission that influence the driving economy.